Material estructurado y nociones lógico-matemáticas en los niños de preparatoria de la Escuela de Educación Básica Ciudad de Loja, en el periodo 2022-2023 - Iñaguazo Guanuche, Rosivel Stefany (2023)
It is important that children develop logical-mathematical notions skills because it allows them to make connections with the world around them and establishes their lived experiences. These skills are essential for the development of intelligence because once the fundamental concepts are mastered, they will be able to solve problems that arise in a logical environment, demonstrating that they are learning and developing your thinking. For this reason, the present investigation was focused on determining how structured material improves logical-mathematical notions in high school children of the Ciudad de Loja Basic Education School. Which had a mixed approach, which allowed to analyze, find out and collect information, a quasi-experimental design was used since the independent variable was manipulated and a descriptive scope, which facilitated obtaining information from the variables, as well as the collection, presentation and description of the results of the instruments applied, in its development process, the methods were used: inductive - deductive, the first facilitated a specific analysis to reach conclusions based on reliable information validating the results obtained in the investigation , and it was complemented with the deductive method, this allowed to give sense and order to the work because it was ordered from the particular to the specific to reach a correct conclusion; analytical - synthetic, allowed us to give way to an individual analysis of the problem variables (logical-mathematical notions) and the solution variable (structured material) in such a way that each of its parts was broken down, likewise it was complemented with the synthetic method that facilitated choosing the main information for the construction of the theoretical framework to give emphasis and relevance to the research topic. In the initial results, the Evamat 0 test or a sample of 23 children, evidencing the difficulty of the children with respect to logical-mathematical notions, locating 74.51% in the low zone and 15.68% in the middle zone. ; However, after having carried out the intervention, it was verified that 80.39% of the children reached the upper zone of their mathematical abilities, concluding the effectiveness of the structured material through the application of a post test, in which it was verified that the Most of the children improved their mathematical ability after having carried out the intervention, children reached the upper zone of their mathematical abilities; thus demonstrating through the results obtained the importance of using structured material as a methodological resource. Keywords: pedagogical resources, problem solving, logical-mathematics, structured material.